The effectiveness of promotional tools to create student’s awareness of Netherlands Maritime Institute of Technology (NMIT) / Norhayati Wahib - Wahib, Norhayati (Faculty of Business and Management, 2010)
The main purpose of this study is to identify the effectiveness of promotional tools to create Student’s awareness of NMIT. The objective of this study is to determine the most suitable types of approach used that creates student’s awareness on NMIT and to establish the most effective of the promotional tools in NMIT. PELORUS has offered a combination of essential programs to a number of the nation’s key industries sub-sectors, which includes shipping, ports and terminals, shipyards, power generation, petroleum refining and gas processing since 1998.The respondents are 60; existing students of NMIT, who study at Kotaraya Campus, Johor Bharu. The researcher had decided to distribute the questionnaire which is primary data. To do the analysis and interpretation of data gathered, the researcher had chosen to use a computer software program which is Statistical Performance for Social Science (SPSS). All primary data are processed and analyzed using Statistical Package for Social Science SPSS (Version 16.0). The results were in form of Reliability Test, Frequency Distribution and Mean. From finding, the researcher found that the most suitable types approach used that creates Student’s awareness on NMIT for direct marketing is internet, for advertising is webpage, for sales promotion is lower cost, for publicity is press conference and for personal selling is face to face by set-up booth. The most effective of promotional tools in NMIT is advertising (webpage and brochure) in creating awareness to students of NMIT.